Eksistensi dan Kewenangan Kementerian Pemberdayaan Perempuan dan Perlindungan Anak Menurut Perpres Nomor 59 Tahun 2015 Tentang KPPPA Dalam Urgensi Pemberdayaan Perempuan dan Perlindungan Anak di Indonesia - Quthub Al Faruqi; Zaitunah Subhan; Abdul Qodir (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
AbstractThis study aims to explain the existence and authority as well as the effectiveness of the performance of the ministry of women empowerment and child protection and its urgency in empowering women and child protection in Indonesia. Researchers use normative research methods with a juridical approach. The results of this study indicate that Presidential Regulation No. 59 of 2015 Concerning the Ministry of Women's Empowerment and Child Protection is indicated to have minimal authority, thus causing ineffective tasks and functions of the Ministry of Women's Empowerment and Child Protection. As a result, many problems cannot be solved. In addition, the Ministry does not have a vertical or representative body in the region which causes the Ministry of Women's Empowerment and Child Protection to have difficulty in resolving technical issues related to women's empowerment and child protection on a national scale. Another problem, the lack of a budget that impacts the integration of central and regional commitments to solve various problems of women and children in Indonesia.Keywords: Women's Empowerment, Child Protection, KPPPA